Organizational Virtuousness and Work Engagement: Mediating Role of Happiness in India. Issue 1 (February 2018) - Singh, Sharda; David, Rajasekhar; Mikkilineni, Sitamma
The Problem: The positive psychology movement has led to an increased attention in organizational virtuousness, engagement, and happiness. Though attention has been devoted to studying the relationship between organizational virtuousness and performance, there is limited research that explores the relationship between employees' perception of organizational virtuousness and work engagement. The Solution: A cross-sectional survey was carried out on a sample of knowledge workers from diverse Indian industries. The findings of the study showed that the employees' perception of organizational virtuousness predicts work engagement not only directly but also indirectly through happiness. The Stakeholders: Managers can nurture organizational virtuousness in organizations to enhance employee happiness and promote a more engaged workforce. Considering the findings of the study, Human Resource Development (HRD) professionals should make the best use of their human capital by fostering positive psychological states such as work engagement.